The securitization and policing of art theft: the case of London - Kerr, John (Ashgate, 2015)
Problematic of art theft -- Situating risk and situating security -- Public police and security -- The private sector: security, investigation and loss adjustment -- Insurance as enabling risk and security -- Governmental nodes enabling security beyond insurance -- The co-production of London art security using nodal governance: the present and future -- Final conclusions